Analysis of Upper Fuel Filter Inventory on Dump Truck Mercedes-Benz AXOR 4843K - Anis Siti Nurrohkayati; Sudirman (Universitas Muhammadiyah Sidoarjo, 2022)
The supply of raw materials is a very important thing in industrial management. Inventory of raw materials can affect the level of productivity of a manufacturing process. This study aims to determine the optimal amount of inventory for the fuel filter on the dump truck. In this study, the data used is secondary data, namely data from company records for 6 months. The data analysis method used is safety stock and reorder point. Based on the results of research and data analysis, the safety stock of upper fuel filters for dump trucks is obtained as much as 8 pcs/month.